Analisis Upaya Pematahan Dormansi Biji Andaliman (Zanthoxylum acanthopodium DC.) dengan Pelukaan dan Perendaman Air Kelapa - Widya Fransiska; Sujarwati Sujarwati (UIN Imam Bonjol Padang, 2023)
Andaliman fruit is a typical food source for the Batak tribe and is usually used as a cooking spice under the name